2016
DOI: 10.1007/s00395-016-0535-8
|View full text |Cite
|
Sign up to set email alerts
|

Atheroprotection through SYK inhibition fails in established disease when local macrophage proliferation dominates lesion progression

Abstract: Macrophages in the arterial intima sustain chronic inflammation during atherogenesis. Under hypercholesterolemic conditions murine Ly6Chigh monocytes surge in the blood and spleen, infiltrate nascent atherosclerotic plaques, and differentiate into macrophages that proliferate locally as disease progresses. Spleen tyrosine kinase (SYK) may participate in downstream signaling of various receptors that mediate these processes. We tested the effect of the SYK inhibitor fostamatinib on hypercholesterolemia-associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 20 publications
(30 reference statements)
2
29
0
Order By: Relevance
“…Robbins and coworkers demonstrated in a hallmark paper in 2013 that local proliferation dominates macrophage accumulation in more advanced atherosclerotic lesions 2 . A similar finding was reported by Lindau et al, who demonstrated that reduced circulating monocyte levels only affected early lesions but not more advanced atherosclerotic lesions 11 . In the present study, Li et al demonstrated that myeloid cell deficiency in PKCδ indeed increase macrophage proliferation in the atherosclerotic lesion (figure) 4 .…”
supporting
confidence: 88%
“…Robbins and coworkers demonstrated in a hallmark paper in 2013 that local proliferation dominates macrophage accumulation in more advanced atherosclerotic lesions 2 . A similar finding was reported by Lindau et al, who demonstrated that reduced circulating monocyte levels only affected early lesions but not more advanced atherosclerotic lesions 11 . In the present study, Li et al demonstrated that myeloid cell deficiency in PKCδ indeed increase macrophage proliferation in the atherosclerotic lesion (figure) 4 .…”
supporting
confidence: 88%
“…These new data demonstrate the embryonal origin of the majority of tissue resident macrophages with self-renewal capabilities, in contrast to macrophages recruited to the tissues after a pathogenic or damaging insult, which in the majority of the cases seem to differentiate from blood monocytes and lack proliferative capacity [48]. Proliferation of macrophages has now been identified in various settings, such as in nematode-infected tissues, obese adipose tissues, glomerulonephritis, atherosclerosis, AIDS-related dementia, and in a variety of murine tumors, when the resident versus inflammatory origin (ontogeny) of these macrophages is in many cases uncertain [49, 50]. Proliferating macrophages have also been recently recognized in human lymphomas and in breast tumors [5154].…”
Section: Discussionmentioning
confidence: 99%
“…In agreement, the SYK inhibitor fostamatinib, administered at the beginning and during feeding Ldlr −/− or Apoe −/− mice a high-cholesterol diet (HCD), reduced monocytosis, vascular inflammation and atherosclerotic lesion size [25, 26]. However, fostamatinib, administered to Apoe −/− mice 8 weeks after the start of HCD feeding, failed to prevent progression of established plaques [26]. In part, this could be explained by degradation of early oxidation products like BEP-CE and diminished role of the TLR4/SYK pathway in advanced atherosclerotic plaques.…”
Section: Biased Activation Of Tlr4 By Oxce and Oxpe Vs Lps In Macropmentioning
confidence: 99%
“…However, under conditions of increased and chronic production of OxCE and OxPE, such as in hyperlipidemia, low-grade but prolonged response would result in chronic inflammation and promote atherosclerosis. In agreement, the SYK inhibitor fostamatinib, administered at the beginning and during feeding Ldlr −/− or Apoe −/− mice a high-cholesterol diet (HCD), reduced monocytosis, vascular inflammation and atherosclerotic lesion size [25, 26]. However, fostamatinib, administered to Apoe −/− mice 8 weeks after the start of HCD feeding, failed to prevent progression of established plaques [26].…”
Section: Biased Activation Of Tlr4 By Oxce and Oxpe Vs Lps In Macropmentioning
confidence: 99%